Halogen-free high-Tg high-heat-resistance transparent substrate

By using halogen-free high Tg high heat-resistant transparent substrate in the display substrate material, combined with the combination design of main slurry, microbead slurry and flame retardant slurry, the existing substrate materials are solved in terms of lightness, thermal stability and cost. The problem of the problem has achieved high Tg and high heat resistance, adapted to the high frequency performance requirements of electronic components, and improved image quality and display accuracy.

CN119144123AInactive Publication Date: 2024-12-17DONGWEI NEW MATERIALS (GUANGZHOU) CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411290124.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2024-12-17
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing display substrate materials such as glass substrates and transparent resin substrates have shortcomings in terms of lightness, thermal stability and production costs, and existing transparent flame retardant polypropylene ultra-thin sheets still have room for improvement in the functional matching of electronic components. .

Method used

Halogen-free high Tg high heat-resistant transparent substrate, including structural layer and fill matrix layer, the fill matrix layer consists of pre-mixed main slurry, microbead slurry and flame retardant slurry. The main slurry contains phenol phenolic epoxy resin , o-cresol epoxy resin and bisphenol A phenolic epoxy resin. The microbead slurry contains inorganic hollow microbeads and polyaryletherketones. The flame retardant slurry contains phosphorus-containing nitrogen-containing phenolic resin. Through scientific and reasonable component design Improve Tg and dielectric performance and adapt to the high-frequency performance requirements of electronic circuits.

Benefits of technology

It realizes high Tg and high heat resistance, reduces the thermal expansion and deformation of the display screen in high temperature environment, ensures image quality and display accuracy, has excellent dielectric properties, heat resistance, flame retardancy and environmental protection, suitable for The performance requirements for electronic components are provided and easy to produce and process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The halogen-free high-Tg high-heat-resistance transparent substrate comprises a structural layer and a filling matrix layer, and preparation raw materials of the filling matrix layer comprise main slurry, microbead slurry and flame-retardant slurry which are prepared by premixing; the main slurry at least comprises 10-45 parts of phenol novolac epoxy resin, 10-30 parts of cresol formaldehyde, 5-25 parts of bisphenol A novolac epoxy resin and 5-15 parts of polyaryletherketone; the microbead slurry at least comprises 15-80 parts of inorganic hollow microbeads and 10-25 parts of polyaryletherketone; the dielectric constant can be 2.0-2.9 at high frequency, Tg can reach up to 189-220 DEG C, the high-Tg and high-heat-resistance display screen material can effectively reduce thermal expansion and deformation of a display screen finished product in a high-temperature environment, and therefore the image quality and display precision of a display screen are guaranteed, and the display screen material has the advantages of being high in Tg and high in heat resistance. And the transparent substrate is adaptive to the performance requirements of electronic components and has better comprehensive performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electronic components, and in particular relates to a halogen-free, high-Tg, and high-heat-resistant transparent substrate. Background Art

[0002] In today's era of rapid development of digitalization and informatization, display screens are important media for information transmission and interaction, and the improvement of their performance and quality is crucial. Therefore, display technology continues to evolve rapidly, and the requirements for display screen substrates are becoming increasingly stringent. The requirements for display screen substrates of electronic components are mainly reflected in the following two aspects:

[0003] On the one hand, various electronic products (especially portable devices and wearable devices) require displays to be thinner, more flexible, and more suitable for the environment. Correspondingly, the display substrate material needs to reduce the thickness and weight as much as possible while ensuring strength and stability.

[0004] On the other hand, as display resolution continues to improve, pixel density increases, and circuit layout becomes more sophisticated, higher requirements are placed on the dimensional stability and thermal stability of the display substrate.

[0005] Currently, the display screen substrate commonly used for electronic components is a glass substrate, but glass substrates have several shortcomings: first, they are relatively brittle and easily break when impacted or bent by external forces. In addition, the thermal expansion coefficient of glass is relatively low. When the thermal expansion coefficient of glass does not match that of other components, stress may be generated in an environment with large temperature changes, causing the substrate to break or performance degradation. Second, the manufacture of glass substrates for electronic components requires high-precision processing equipment and complex process flows, resulting in high production costs. Finally, for electronic devices that pursue lightweight and thinness, the weight of the glass substrate may become a limiting factor.

[0006] In this field, there is also technology for making transparent substrates using PA resin, PI resin, epoxy resin, etc. Compared with glass substrates, display screen substrates made of transparent resins have the advantages of lighter weight and better electromagnetic shielding performance, but the glass transition temperature (Tg) is low, and the temperature range in which they can be used after being made into electronic components is relatively limited.

[0007] That is, the transparent substrate materials commonly used in this field currently have their own advantages and disadvantages, and it is necessary to develop a transparent substrate material with better comprehensive performance.

[0008] Patent document with application number 202410398566.8 discloses a transparent flame-retardant polypropylene ultra-thin sheet and a preparation method thereof. The transparent flame-retardant polypropylene ultra-thin sheet includes the following raw materials: polypropylene, organophosphorus flame retardant, transmittance enhancer, nano-inorganic additive, modified polyethylene glycol, antioxidant, modified nano-mullite, and lubricant.

[0009] The above-mentioned existing technology starts from the technical idea of ​​improving the flame retardancy of the transparent substrate and makes improvements. It reaches the UL94V-0 flame retardancy level in the thickness range of 0.2-1.0mm, which is better than ordinary polypropylene and polypropylene ultra-thin sheets with added flame retardants. The preparation method is environmentally friendly and does not require the use of halogen flame retardants, thus avoiding the environmental pollution and human harm of halogen flame retardants. At the same time, the organophosphorus flame retardants and nano-inorganic additives used are low-toxic or non-toxic substances, which are harmless to the environment and human body.

[0010] However, there is still room for improvement in the transparent plate of the prior art in terms of matching the functions of electronic components. Summary of the invention

[0011] In view of the problems in the related art, the present invention proposes a halogen-free, high Tg and high heat-resistant transparent substrate to overcome the above technical problems existing in the existing related art.

[0012] The technical solution of the present invention is achieved in this way:

[0013] A halogen-free, high-Tg, high-heat-resistant transparent substrate, comprising a structural layer and a filling matrix layer, wherein the filling matrix layer completely covers and fills the structural layer;

[0014] The raw materials for preparing the filling matrix layer include a main slurry, a microbead slurry and a flame retardant slurry that are pre-mixed;

[0015] The main slurry contains at least 10 to 45 parts of phenol novolac epoxy resin, 10 to 30 parts of o-cresol novolac epoxy resin, 5 to 25 parts of bisphenol A novolac epoxy resin and 5 to 15 parts of polyaryletherketone;

[0016] The microbead slurry contains at least 15 to 80 parts of inorganic hollow microbeads and 10 to 25 parts of polyaryletherketone;

[0017] The flame retardant slurry contains at least 10 to 35 parts of phosphorus- and nitrogen-containing phenolic resin.

[0018] With the continuous advancement of electronic circuit technology, the upper limit of the operating frequency of active devices is also continuously increasing. To produce a transparent substrate that meets the requirements of electronic circuits, the present invention first starts with increasing the Tg (glass transition temperature). The high Tg transparent substrate can better match the high-frequency performance requirements of components. The present invention can achieve a dielectric constant of 2. 0 ~2.9, Tg can be as high as 189~220 ℃, the present invention with high Tg and high heat resistance can also effectively reduce the thermal expansion and deformation of the finished display screen in a high temperature environment, thereby ensuring the image quality and display accuracy of the display screen.

[0019] Through scientific and reasonable component design, the present invention has excellent dielectric properties, heat resistance, flame retardancy and environmental protection, is easy to produce and process, and is a transparent substrate that meets the performance requirements of electronic components and has better comprehensive performance.

[0020] Preferably, the outer diameter d of the inorganic hollow microbeads is 80-150 nm, the wall thickness of the inorganic hollow microbeads is set to h, and 1 / 10d≤h≤1 / 6d.

[0021] More preferably, the inorganic hollow microspheres are mullite hollow microspheres or silica hollow microspheres.

[0022] Preferably, the main slurry further comprises 1 to 3 parts by weight of a dispersant. Specifically, the dispersant is a product of model number HyPer C100 developed and produced by Wuhan Hyperbranched Resin Technology Co., Ltd.

[0023] Preferably, the microbead slurry further comprises 1 to 3 parts by weight of an anhydride curing agent with a furan ring and 1 to 3 parts by weight of a dispersant. Specifically, the dispersant is a product of model HyPer C100 developed and produced by Wuhan Hyperbranched Resin Technology Co., Ltd.

[0024] Specifically, the anhydride curing agent with a furan ring is a CL-BTH model product developed and produced by Shin-Etsu of Japan.

[0025] Preferably, the flame retardant slurry further comprises 3 to 15 parts by weight of linear phenol formaldehyde and 1 to 3 parts by weight of resorcinol bis[di(2,6-dimethylphenyl)phosphate].

[0026] Preferably, the polyaryletherketone is phenolphthalein polyaryletherketone, specifically phenolphthalein polyaryletherketone PEKC developed and produced by Zhejiang Palco New Materials Co., Ltd.

[0027] More preferably, the phosphorus-nitrogen-containing phenolic resin is a phosphorus-nitrogen flame retardant of model JA-FR100 produced by Guangzhou Jiabai Electronic Technology Co., Ltd.

[0028] Preferably, the method for preparing the slurry for filling the matrix layer comprises the following steps:

[0029] S1. Each component of the main slurry is added to the first mixing device according to the preset weight proportions for premixing, with a stirring speed of 60 to 300 r / min for 1 to 4 hours to obtain the main slurry for standby use;

[0030] S2, adding each component of the microbead slurry to the second mixing equipment according to the preset weight proportions for premixing, stirring at a speed of 150-450r / min, stirring for 1-4h, and a vibration frequency of 15-25KHz, and mixing and resonating to obtain a microbead slurry for standby use;

[0031] S3, adding each component of the flame retardant slurry according to a preset weight portion into a third mixing device for premixing to obtain a flame retardant slurry;

[0032] S4, adding the flame retardant slurry prepared in S3 into the first mixing equipment in batches and mixing with the main slurry, stirring at a speed of 100 to 800 r / min for 2 to 5 hours;

[0033] S5. Add the microbead slurry obtained in S2 into the first mixing equipment for mixing at a stirring speed of 300-600 r / min and stir for 3-6 hours to obtain a composite slurry for forming the filling matrix layer.

[0034] Preferably, the structural layer is electronic grade glass fiber cloth, and the weight of the electronic grade glass fiber cloth is 10-40wt% of the composite slurry;

[0035] The electronic grade glass fiber cloth has a transmittance of ≥90% under visible light of 400-700nm;

[0036] The method for forming the structural layer and the filling matrix layer is as follows: the electronic grade glass fiber cloth is completely immersed in the composite slurry for 3 to 5 minutes, and then pressed and cured to form a semi-cured sheet with a structural layer and a filling matrix layer.

[0037] The electronic grade glass fiber cloth can be one of NE-glass fiber cloth, E-glass fiber cloth, and flat E-glass fiber cloth, preferably NE-glass fiber cloth.

[0038] Preferably, the weaving specification of the electronic grade glass fiber cloth is 106 or 1080, and the parameters are shown in the following table.

[0039]

[0040] Preferably, a conductive layer is laminated on one or both sides of the outer surface of the prepreg sheet, and the conductive layer has a hollow structure;

[0041] The conductive layer is a copper foil with a thickness of 55 to 70 μm;

[0042] The lamination operation is as follows: the conductive layer is covered on the outer surface of the semi-cured sheet, and the lamination is performed for 3 to 5 hours at a lamination temperature of 100 to 260°C.

[0043] In actual production, the conductive copper foil is subjected to graphic etching treatment as needed to form a transparent hollow pattern to achieve transparent display of the non-conductive area. DETAILED DESCRIPTION

[0045] Example 1

[0046] A halogen-free, high Tg, high heat-resistant transparent substrate, the preparation method is as follows:

[0047] S1. Prepare the main slurry: including 25kg phenol novolac epoxy resin, 20kg o-cresol novolac epoxy resin, 15kg bisphenol A novolac epoxy resin and 10kg polyaryletherketone.

[0048] The polyaryletherketone is phenolphthalein-based polyaryletherketone PEKC developed and produced by Zhejiang Palco New Materials Co., Ltd.

[0049] The components of the main slurry are added into the stirring reactor A according to the preset weight for premixing, and the stirring speed is 200 r / min, and the stirring is carried out for 2 hours to obtain the main slurry for standby use.

[0050] S2. Prepare microbead slurry: including 40 kg of inorganic hollow microbeads (silicon dioxide hollow microbeads), 15 kg of polyaryletherketone and 2 kg of anhydride curing agent with a furan ring.

[0051] The outer diameter d of the inorganic hollow microbeads is 120 nm, and the wall thickness h of the inorganic hollow microbeads is 15 nm.

[0052] The polyaryletherketone is phenolphthalein-based polyaryletherketone PEKC developed and produced by Zhejiang Palco New Materials Co., Ltd.

[0053] The anhydride curing agent with a furan ring is a CL-BTH model product developed and produced by Shin-Etsu of Japan.

[0054] The components of the microbead slurry are added into an ultrasonic stirring reactor according to a preset weight for premixing, with a stirring speed of 300 r / min, stirring for 2 h, a vibration frequency of 20 KHz, and blending resonance to obtain a microbead slurry for standby use.

[0055] S3. Divide 20 kg of phosphorus- and nitrogen-containing phenolic resin into three substantially equal batches and add them successively into stirred reactor A to mix with the main slurry at a stirring speed of 350 r / min for 3.5 h.

[0056] The phosphorus-nitrogen-containing phenolic resin is a phosphorus-nitrogen flame retardant of model JA-FR100 produced by Guangzhou Jiabai Electronic Technology Co., Ltd.

[0057] S4, adding the microbead slurry obtained in S2 into the stirring reactor A for mixing, with a stirring speed of 450 r / min, and stirring for 3.5 hours to obtain a composite slurry for forming the filling matrix layer.

[0058] S5. The composite slurry is transported to the dipping tank of the gluing machine through a feeding pipe, and the electronic grade glass fiber cloth is completely immersed in the composite slurry for 4 minutes, and then pressed, dried and cooled to form a semi-cured sheet with a thickness of 120 μm.

[0059] The weight of the electronic grade glass fiber cloth is 30wt% of the composite slurry.

[0060] The visible light (400-700nm) transmittance of the electronic grade glass fiber cloth is ≥90%.

[0061] The weaving specification is 108.

[0062]

[0063] The electronic grade glass fiber cloth is used as the structural layer and the cured composite slurry is used as the filling matrix layer, and the filling matrix layer completely covers and fills the structural layer; the raw materials for preparing the filling matrix layer include pre-mixed main slurry, microbead slurry and flame retardant slurry.

[0064] S7. Cover the outer surfaces of both sides of the semi-cured sheet with a conductive layer (copper foil with a thickness of 60 μm), transport it to a high-temperature pressing device, press it at a pressing temperature of 180° C. for 4 hours, and then cool it to room temperature.

[0065] Example 2

[0066] A halogen-free, high Tg, high heat-resistant transparent substrate, the preparation method is as follows:

[0067] S1. Prepare the main slurry: including 10kg phenol novolac epoxy resin, 10kg o-cresol novolac epoxy resin, 5kg bisphenol A novolac epoxy resin, 5kg polyaryletherketone and 1kg dispersant.

[0068] The dispersant is a product of model HyPer C100 developed and produced by Wuhan Hyperbranched Resin Technology Co., Ltd.

[0069] The polyaryletherketone is phenolphthalein-based polyaryletherketone PEKC developed and produced by Zhejiang Palco New Materials Co., Ltd.

[0070] The components of the main slurry were added into the stirring reactor A according to the preset weight for premixing, with the stirring speed of 100 r / min and stirring for 1 h to obtain the main slurry for standby use.

[0071] S2. Prepare microbead slurry: including 15 kg of inorganic hollow microbeads (mullite hollow microbeads), 10 kg of polyaryletherketone, 1 kg of anhydride curing agent with furan ring and 1 kg of dispersant.

[0072] The outer diameter d of the inorganic hollow microbeads is 80 nm, and the wall thickness h of the inorganic hollow microbeads is 10 nm.

[0073] The polyaryletherketone is phenolphthalein-based polyaryletherketone PEKC developed and produced by Zhejiang Palco New Materials Co., Ltd.

[0074] The dispersant is a product of model HyPer C100 developed and produced by Wuhan Hyperbranched Resin Technology Co., Ltd.

[0075] The anhydride curing agent with a furan ring is a CL-BTH model product developed and produced by Shin-Etsu of Japan.

[0076] The components of the microbead slurry are added into an ultrasonic stirring reactor according to a preset weight for premixing, with a stirring speed of 150 r / min, stirring for 1 hour, a vibration frequency of 25 KHz, and blending resonance to obtain a microbead slurry for standby use.

[0077] S3. Prepare flame retardant slurry: including 10kg phosphorus- and nitrogen-containing phenolic resin, 3kg linear phenol formaldehyde and 1kg resorcinol bis[di(2,6-dimethylphenyl) phosphate].

[0078] The phosphorus-nitrogen-containing phenolic resin is a phosphorus-nitrogen flame retardant of model JA-FR100 produced by Guangzhou Jiabai Electronic Technology Co., Ltd.

[0079] The components of the flame retardant slurry are added into a stirred reactor B according to a preset weight for premixing to obtain a flame retardant slurry.

[0080] S4. Divide the flame retardant slurry obtained in S3 into three batches of substantially equal amounts and add them into the stirred reactor A successively to mix with the main slurry at a stirring speed of 100 r / min for 2 h.

[0081] S5. Add the microbead slurry obtained in S2 into the stirring reactor A for mixing at a stirring speed of 300 r / min and stir for 3 hours to obtain a composite slurry for forming the filling matrix layer.

[0082] S6. The composite slurry is transported to the impregnation tank of the gluing machine through a feeding pipe, and the electronic grade glass fiber cloth is completely immersed in the composite slurry for 3 minutes, and then pressed, dried and cooled to form a semi-cured sheet with a thickness of 120 μm.

[0083] The weight of the electronic grade glass fiber cloth is 30wt% of the composite slurry.

[0084] The visible light (400-700nm) transmittance of the electronic grade glass fiber cloth is ≥90%.

[0085] The weaving specification is 106.

[0086]

[0087] The electronic grade glass fiber cloth is used as the structural layer and the cured composite slurry is used as the filling matrix layer, and the filling matrix layer completely covers and fills the structural layer; the raw materials for preparing the filling matrix layer include pre-mixed main slurry, microbead slurry and flame retardant slurry.

[0088] S7. Cover the outer surfaces of both sides of the semi-cured sheet with a conductive layer (copper foil with a thickness of 60 μm), transport it to a high-temperature pressing device, press it at a pressing temperature of 100° C. for 3 hours, and then cool it to room temperature.

[0089] Example 3

[0090] A halogen-free, high Tg, high heat-resistant transparent substrate, the preparation method is as follows:

[0091] S1. Prepare the main slurry: including 25kg phenol novolac epoxy resin, 20kg o-cresol novolac epoxy resin, 15kg bisphenol A novolac epoxy resin, 10kg polyaryletherketone and 2kg dispersant.

[0092] The dispersant is a product of model HyPer C100 developed and produced by Wuhan Hyperbranched Resin Technology Co., Ltd.

[0093] The polyaryletherketone is phenolphthalein-based polyaryletherketone PEKC developed and produced by Zhejiang Palco New Materials Co., Ltd.

[0094] The components of the main slurry are added into the stirring reactor A according to the preset weight for premixing, and the stirring speed is 200 r / min, and the stirring is carried out for 2 hours to obtain the main slurry for standby use.

[0095] S2. Prepare microbead slurry: including 40 kg of inorganic hollow microbeads (mullite hollow microbeads), 15 kg of polyaryletherketone, 2 kg of anhydride curing agent with furan ring and 2 kg of dispersant.

[0096] The outer diameter d of the inorganic hollow microbeads is 120 nm, and the wall thickness h of the inorganic hollow microbeads is 15 nm.

[0097] The polyaryletherketone is phenolphthalein-based polyaryletherketone PEKC developed and produced by Zhejiang Palco New Materials Co., Ltd.

[0098] The dispersant is a product of model HyPer C100 developed and produced by Wuhan Hyperbranched Resin Technology Co., Ltd.

[0099] The anhydride curing agent with a furan ring is a CL-BTH model product developed and produced by Shin-Etsu of Japan.

[0100] The components of the microbead slurry are added into an ultrasonic stirring reactor according to a preset weight for premixing, with a stirring speed of 300 r / min, stirring for 2 h, a vibration frequency of 25 KHz, and blending resonance to obtain a microbead slurry for standby use.

[0101] S3. Prepare flame retardant slurry: including 20kg phosphorus- and nitrogen-containing phenolic resin, 10kg linear phenol formaldehyde and 2kg resorcinol bis[di(2,6-dimethylphenyl) phosphate].

[0102] The phosphorus-nitrogen-containing phenolic resin is a phosphorus-nitrogen flame retardant of model JA-FR100 produced by Guangzhou Jiabai Electronic Technology Co., Ltd.

[0103] The components of the flame retardant slurry are added into a stirred reactor B according to a preset weight for premixing to obtain a flame retardant slurry.

[0104] S4. Divide the flame retardant slurry obtained in S3 into three batches of substantially equal amounts and add them into the stirred reactor A in succession to mix with the main slurry. Stir at a speed of 350 r / min for 3.5 h.

[0105] S5. Add the microbead slurry obtained in S2 into the stirring reactor A for mixing at a stirring speed of 450 r / min and stir for 3.5 hours to obtain a composite slurry for forming the filling matrix layer.

[0106] S6. The composite slurry is transported to the dipping tank of the gluing machine through a feeding pipe, and the electronic grade glass fiber cloth is completely immersed in the composite slurry for 4 minutes, and then pressed, dried and cooled to form a semi-cured sheet with a thickness of 120 μm.

[0107] The weight of the electronic grade glass fiber cloth is 30wt% of the composite slurry.

[0108] The visible light (400-700nm) transmittance of the electronic grade glass fiber cloth is ≥90%.

[0109] The weaving specification is 106.

[0110]

[0111] The electronic grade glass fiber cloth is used as the structural layer and the cured composite slurry is used as the filling matrix layer, and the filling matrix layer completely covers and fills the structural layer; the raw materials for preparing the filling matrix layer include pre-mixed main slurry, microbead slurry and flame retardant slurry.

[0112] S7. Cover the outer surfaces of both sides of the semi-cured sheet with a conductive layer (copper foil with a thickness of 60 μm), transport it to a high-temperature pressing device, press it at a pressing temperature of 180° C. for 4 hours, and then cool it to room temperature.

[0113] Example 4

[0114] A halogen-free, high Tg, high heat-resistant transparent substrate, the preparation method is as follows:

[0115] S1. Prepare the main slurry: including 45kg phenol novolac epoxy resin, 30kg o-cresol novolac epoxy resin, 25kg bisphenol A novolac epoxy resin, 15kg polyaryletherketone and 3kg dispersant.

[0116] The dispersant is a product of model HyPer C100 developed and produced by Wuhan Hyperbranched Resin Technology Co., Ltd.

[0117] The polyaryletherketone is phenolphthalein-based polyaryletherketone PEKC developed and produced by Zhejiang Palco New Materials Co., Ltd.

[0118] The components of the main slurry were added into the stirring reactor A according to the preset weight for premixing, with the stirring speed of 300 r / min and stirring for 4 h to obtain the main slurry for standby use.

[0119] S2. Prepare microbead slurry: including 80 kg of inorganic hollow microbeads (mullite hollow microbeads), 25 kg of polyaryletherketone, 3 kg of anhydride curing agent with furan ring and 3 kg of dispersant.

[0120] The outer diameter d of the inorganic hollow microbeads is 150 nm, and the wall thickness h of the inorganic hollow microbeads is 20 nm.

[0121] The polyaryletherketone is phenolphthalein-based polyaryletherketone PEKC developed and produced by Zhejiang Palco New Materials Co., Ltd.

[0122] The dispersant is a product of model HyPer C100 developed and produced by Wuhan Hyperbranched Resin Technology Co., Ltd.

[0123] The anhydride curing agent with a furan ring is a CL-BTH model product developed and produced by Shin-Etsu of Japan.

[0124] The components of the microbead slurry are added into an ultrasonic stirring reactor according to a preset weight for premixing, with a stirring speed of 450 r / min, stirring for 4 hours, a vibration frequency of 20 KHz, and blending resonance to obtain a microbead slurry for standby use.

[0125] S3. Prepare flame retardant slurry: including 35kg phosphorus- and nitrogen-containing phenolic resin, 15kg linear phenol formaldehyde and 3kg resorcinol bis[di(2,6-dimethylphenyl) phosphate].

[0126] The phosphorus-nitrogen-containing phenolic resin is a phosphorus-nitrogen flame retardant of model JA-FR100 produced by Guangzhou Jiabai Electronic Technology Co., Ltd.

[0127] The components of the flame retardant slurry are added into a stirred reactor B according to a preset weight for premixing to obtain a flame retardant slurry.

[0128] S4. Divide the flame retardant slurry obtained in S3 into three batches of substantially equal amounts and add them into the stirred reactor A in succession to mix with the main slurry at a stirring speed of 800 r / min for 5 hours.

[0129] S5. Add the microbead slurry obtained in S2 into the stirring reactor A for mixing at a stirring speed of 600 r / min and stir for 6 hours to obtain a composite slurry for forming the filling matrix layer.

[0130] S6. The composite slurry is transported to the impregnation tank of the gluing machine through a feeding pipe, and the electronic grade glass fiber cloth is completely immersed in the composite slurry for 5 minutes, and then pressed, dried and cooled to form a semi-cured sheet with a thickness of 120 μm.

[0131] The weight of the electronic grade glass fiber cloth is 30wt% of the composite slurry.

[0132] The visible light (400-700nm) transmittance of the electronic grade glass fiber cloth is ≥90%.

[0133] The weaving specification is 106.

[0134]

[0135] The electronic grade glass fiber cloth is used as the structural layer and the cured composite slurry is used as the filling matrix layer, and the filling matrix layer completely covers and fills the structural layer; the raw materials for preparing the filling matrix layer include pre-mixed main slurry, microbead slurry and flame retardant slurry.

[0136] S7. Cover the single-side / double-side outer surface of the semi-cured sheet with a conductive layer (copper foil with a thickness of 60 μm), transport it to a high-temperature pressing device, press it at a pressing temperature of 250° C. for 5 hours, and then cool it to room temperature.

[0137] Comparative Example 1

[0138] The preparation method of this comparative example is as follows:

[0139] S1. Configuration components:

[0140] 40kg inorganic hollow microspheres (mullite hollow microspheres, outer diameter d is 120nm, wall thickness h is 15nm),

[0141] 25kg phenol novolac epoxy resin,

[0142] 20kg o-cresol epoxy resin,

[0143] 20kg phosphorus- and nitrogen-containing phenolic resin,

[0144] 15kg bisphenol A novolac epoxy resin,

[0145] 25kg polyaryletherketone,

[0146] 10kg linear phenol formaldehyde,

[0147] 4kg dispersant,

[0148] 2kg of anhydride curing agent with furan ring,

[0149] 2 kg resorcinol bis[di(2,6-dimethylphenyl)phosphate].

[0150] The dispersant is a product of model HyPer C100 developed and produced by Wuhan Hyperbranched Resin Technology Co., Ltd.

[0151] The polyaryletherketone is phenolphthalein-based polyaryletherketone PEKC developed and produced by Zhejiang Palco New Materials Co., Ltd.

[0152] The anhydride curing agent with a furan ring is a CL-BTH model product developed and produced by Shin-Etsu of Japan.

[0153] The phosphorus-nitrogen-containing phenolic resin is a phosphorus-nitrogen flame retardant of model JA-FR100 produced by Guangzhou Jiabai Electronic Technology Co., Ltd.

[0154] S2. Each component is added into an ultrasonic stirring reactor according to a preset weight for premixing, with a stirring speed of 300 r / min, stirring for 6 hours, a vibration frequency of 20 KHz, and a composite slurry is obtained by blending and resonance.

[0155] S3. The composite slurry is transported to the impregnation tank of the gluing machine through a feeding pipe, and the electronic grade glass fiber cloth is completely immersed in the composite slurry for 4 minutes, and then pressed, dried and cooled to form a semi-cured sheet with a thickness of 120 μm.

[0156] The weight of the electronic grade glass fiber cloth is 30wt% of the composite slurry.

[0157] The visible light (400-700nm) transmittance of the electronic grade glass fiber cloth is ≥90%.

[0158] The weaving specification is 106.

[0159]

[0160] S4. Cover the outer surfaces of both sides of the semi-cured sheet with a conductive layer (copper foil with a thickness of 60 μm), transport it to a high-temperature pressing device, press it at a pressing temperature of 180° C. for 4 hours, and then cool it to room temperature.

[0161] Comparative Example 2

[0162] Compared with Example 4, the inorganic hollow microspheres are 90 kg; the other components and operations are the same.

[0163] Comparative Example 3

[0164] Compared with Example 3, the polyaryletherketone adopts polyaryletherketone PEEK produced by Victrex, UK; the other components and operations are the same.

[0165] Comparative Example 4

[0166] Compared with Example 3, the dispersant is cyclobutylene terephthalate (CBT) resin; the other components and operations are the same.

[0167] Comparative Example 5

[0168] Compared with Example 3, the flame retardant slurry is replaced by SPB-100 halogen-free flame retardant; the other components and operations are the same.

[0169] Performance Testing

[0170] Examples 1 to 4, comparative examples 1 to 5, PA resin, PI resin, epoxy resin, glass, and copper foil were made into test samples suitable for test experiments, and the following test experiments were carried out.

[0171] (1) The glass transition temperature (Tg) and the thermal expansion coefficient were determined by static thermomechanical analysis (TMA).

[0172] (2) Determination of dielectric constant:

[0173] The dielectric constant is determined by the resonant cavity test method, which uses a network analyzer to measure the resonant frequency and Q value of the resonant cavity fixture, which is set up blank at the beginning of the test and then loaded with the sample to be tested. When the volume of the sample and other parameters of the resonant cavity are known, the dielectric constant is calculated from these measurements.

[0174] (3) Determination of transmittance:

[0175] The transmittance of 550nm visible light is measured by a transmittance tester.

[0176] (4) Determine the density.

[0177] The test results are shown in the following table:

[0178]

[0179] From the above table, we can see that:

[0180] The Tg of Examples 1 to 4 is 189-220°C, indicating that the present invention is indeed a high Tg material with good mechanical strength, excellent high-temperature thermal stability, thermal expansion coefficient stability, etc. Although the Tg is slightly lower than that of PI resin, the thermal expansion coefficient of Examples 1 to 4 ranges from 11 to 13. Compared with other commonly used materials, the thermal expansion coefficient of the metal conductive layer "copper foil" of the present invention is most suitable for 16 to 18, which can avoid stress caused by mismatch of thermal expansion coefficients between the substrate and the copper foil in an environment with large temperature changes, thereby ensuring the image quality and display accuracy of the display screen;

[0181] At the same time, compared with commonly used materials, Examples 1 to 4 have lower dielectric constants, which can reduce dielectric loss; the density of Examples 1 to 4 is much lower than that of glass, which is equivalent to commonly used resin materials, and is conducive to making thin electronic components; the transmittance ≥ 70 meets the transparency requirements of most electronic display screens.

[0182] From the data of comparative example 1, it can be seen that not performing the premixing step has an adverse effect on the performance of the substrate; from comparative example 2, it can be seen that if the proportion of inorganic hollow microspheres exceeds the setting of the present invention, it will lead to a decrease in performance, that is, the weight proportion of inorganic hollow microspheres is a specific design of the present invention. The inventors also studied and compared several commonly used additives on the market and found that the selection of additives will also have a certain impact on the performance of the present invention. This may be caused by the difference in compatibility between different additives and the resin system designed by the present invention, which needs to be studied.

[0183] In summary, although not all properties of the present invention far exceed those of conventional materials, all properties of the present invention have reached excellent levels, and it is a transparent substrate with better comprehensive performance.

[0184] According to the disclosure and teaching of the above description, those skilled in the art to which the present invention belongs may also change and modify the above implementation modes. Therefore, the present invention is not limited to the specific implementation modes disclosed and described above, and some modifications and changes to the present invention should also fall within the protection scope of the claims of the present invention. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present invention.

Claims

1. A halogen-free, high Tg, high heat-resistant transparent substrate, characterized in that: It comprises a structural layer and a filling matrix layer, wherein the filling matrix layer completely covers and fills the structural layer; The raw materials for preparing the filling matrix layer include a main slurry, a microbead slurry and a flame retardant slurry that are pre-mixed; The main slurry contains at least 10 to 45 parts of phenol novolac epoxy resin, 10 to 30 parts of o-cresol novolac epoxy resin, 5 to 25 parts of bisphenol A novolac epoxy resin and 5 to 15 parts of polyaryletherketone; The microbead slurry contains at least 15 to 80 parts of inorganic hollow microbeads and 10 to 25 parts of polyaryletherketone; The flame retardant slurry contains at least 10 to 35 parts of phosphorus- and nitrogen-containing phenolic resin.

2. The halogen-free, high Tg, high heat-resistant transparent substrate according to claim 1, characterized in that: The main slurry further comprises 1 to 3 parts by weight of a dispersant.

3. The halogen-free, high Tg, high heat-resistant transparent substrate according to claim 1, characterized in that: The microbead slurry also contains 1 to 3 parts by weight of an acid anhydride curing agent with a furan ring and 1 to 3 parts by weight of a dispersant; The outer diameter d of the inorganic hollow microspheres is 80-150 nm, and the wall thickness of the inorganic hollow microspheres is set to h, 1 / 10d≤h≤1 / 6d; The inorganic hollow microspheres are mullite hollow microspheres or silicon dioxide hollow microspheres.

4. The halogen-free, high Tg, high heat-resistant transparent substrate according to claim 1, characterized in that: The flame retardant slurry further comprises 3 to 15 parts by weight of linear phenol formaldehyde and 1 to 3 parts by weight of resorcinol bis[di(2,6-dimethylphenyl)phosphate].

5. The halogen-free, high Tg, high heat-resistant transparent substrate according to any one of claims 1 to 4, characterized in that: The polyaryletherketone is phenolphthalein-based polyaryletherketone PEKC developed and produced by Zhejiang Palco New Materials Co., Ltd.

6. The halogen-free, high Tg, high heat-resistant transparent substrate according to any one of claims 1 to 4, characterized in that: The phosphorus-nitrogen-containing phenolic resin is a phosphorus-nitrogen flame retardant of model JA-FR100 produced by Guangzhou Jiabai Electronic Technology Co., Ltd.

7. The halogen-free, high Tg, high heat-resistant transparent substrate according to claim 2 or 3, characterized in that: The dispersant is a product of model HyPer C100 developed and produced by Wuhan Hyperbranched Resin Technology Co., Ltd.

8. The halogen-free, high Tg, high heat-resistant transparent substrate according to any one of claims 1 to 4, characterized in that: The method for preparing the slurry for filling the matrix layer comprises the following steps: S1. Each component of the main slurry is added to the first mixing device according to the preset weight proportions for premixing, with a stirring speed of 60 to 300 r / min for 1 to 4 hours to obtain the main slurry for standby use; S2, adding each component of the microbead slurry to the second mixing equipment according to the preset weight proportions for premixing, stirring at a speed of 150-450r / min, stirring for 1-4h, and a vibration frequency of 15-25KHz, and mixing and resonating to obtain a microbead slurry for standby use; S3, adding each component of the flame retardant slurry according to a preset weight portion into a third mixing device for premixing to obtain a flame retardant slurry; S4, adding the flame retardant slurry prepared in S3 into the first mixing equipment in batches and mixing with the main slurry, stirring at a speed of 100 to 800 r / min for 2 to 5 hours; S5. Add the microbead slurry obtained in S2 into the first mixing equipment for mixing at a stirring speed of 300-600 r / min and stir for 3-6 hours to obtain a composite slurry for forming the filling matrix layer.

9. The halogen-free, high Tg, high heat-resistant transparent substrate according to claim 8, characterized in that: The structural layer is electronic grade glass fiber cloth, and the weight of the electronic grade glass fiber cloth is 10-40wt% of the composite slurry; The electronic grade glass fiber cloth has a transmittance of ≥90% under visible light of 400-700nm; The method for forming the structural layer and the filling matrix layer is as follows: the electronic grade glass fiber cloth is completely immersed in the composite slurry for 3 to 5 minutes, and then pressed and cured to form a semi-cured sheet with a structural layer and a filling matrix layer.

10. The halogen-free, high Tg, high heat-resistant transparent substrate according to claim 9, characterized in that: A conductive layer is laminated on one or both sides of the outer surface of the prepreg sheet, and the conductive layer has a hollow structure; The conductive layer is a copper foil with a thickness of 55 to 70 μm; The lamination operation is as follows: the conductive layer is covered on the outer surface of the semi-cured sheet, and the lamination is performed for 3 to 5 hours at a lamination temperature of 100 to 260°C.

Citation Information

Patent Citations

  • Transparent flame-retardant polypropylene ultrathin plate

    CN118108996A

  • Resin composition, prepreg, and film

    CN104903380A

  • Resin compositions and process for forming transparent thin films

    US5180794A